AN ANALYSIS OF MAIN CHARACTER'S MOTIVATION IN JACK LONDON'S SHORT STORY ENTITLED TO BUILD A FIRE - Anak Agung Bagus Ari Sentana; Marnina Marnina; Sri Winarsih (Musamus Journal of Language and Literature, 2023)
This research examines psychology which is motivation of the main character in the short story. Motivation is a state inside us that demands a change, whether in ourselves or in our surroundings. Moreover, motivation is a person's desire to achieve the needs that they want. This research focuses on the types of motivation and the hierarchy needs that the main character try to achieve in the short story.This research is a qualitative research and the method used in this research is a qualitative descriptive method. In addition, the theories used in this research have two theories. The first theory was the theory of motivation proposed by Ryan and Decy to analyze the types of motivation found in To Build a Fire short story. The second theory is the theory of hierarchy needs proposed by Abraham Maslow to analyze the needs that the main character try to achieve.The results of this research indicate that there are two types of motivation which consist of intrinsic motivation, they are five data of behavior and five data of passion. In addition, they are extrinsic motivation which are three data of status and two data of rewards. Meanwhile, there are five types of hierarchy needs which consist of three data of psychological needs, four data of safety needs, three data of love and belongingness needs, two data of self-esteem needs and three data of cognitive needs.